Analysis of the Influence of Facility Quality and Health Worker Service Quality on Outpatient Satisfaction at H. Padjonga Daeng Ngalle Regional General Hospital, Takalar - Mangindara Mangindara; Ruqaiyah Ruqaiyah; Ali Imran; Riska Ayu Adelia (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
The availability of adequate facilities and the quality of healthcare services are crucial determinants of patient satisfaction, particularly in outpatient care. H. Padjonga Daeng Ngalle Regional General Hospital still faces several infrastructural and service challenges, such as ceiling leaks during the rainy season and limited seating in waiting areas, which may reduce patient comfort. This study aimed to analyze the influence of facility quality and healthcare service quality on outpatient satisfaction at H. Padjonga Daeng Ngalle Regional General Hospital in 2025. A quantitative approach with a cross-sectional design was employed, involving 362 randomly selected respondents. Data were collected through a validated and reliable questionnaire and analyzed using the chi-square test with SPSS software. The results showed a significant relationship between facility quality (p = 0.000; PR = 2.36; 95% CI: 1.78–3.12) and healthcare service quality (p = 0.000; PR = 2.91; 95% CI: 2.04–4.15) with outpatient satisfaction (p < 0.05). These findings indicate that both facility and service quality substantially influence outpatient satisfaction. Therefore, hospital management should prioritize improving physical facilities, service systems, and healthcare personnel competence to enhance patient satisfaction sustainably.